2011
DOI: 10.1111/j.1523-5378.2011.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Incidence of Helicobacter pylori Infection in a Healthy Pediatric Population in the Lisbon Area

Abstract: The prevalence of H. pylori infection in the Portuguese pediatric population is still high. Although this study confirmed that the highest acquisition rate occurs at young age, it showed that in high-prevalence populations, older children can also acquire H. pylori infection at a rate similar to that of young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 57 publications
7
47
1
5
Order By: Relevance
“…In Portugal, the first national study addressing H. pylori prevalence (assessed by serology), published in 1994, showed that the prevalence of infection among children aged between 3 and 14 years was 46.2% [26]. In a recent study conducted in the south of Portugal, the prevalence of H. pylori infection (assessed by stool antigen test) in children aged between 3 and 14 years of age was 39.3%, and 51.5% in children aged between 11 and 15 years [27]. The prevalence found in our study is higher, which explains the higher gastric cancer incidence found in the North of Portugal [13,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Portugal, the first national study addressing H. pylori prevalence (assessed by serology), published in 1994, showed that the prevalence of infection among children aged between 3 and 14 years was 46.2% [26]. In a recent study conducted in the south of Portugal, the prevalence of H. pylori infection (assessed by stool antigen test) in children aged between 3 and 14 years of age was 39.3%, and 51.5% in children aged between 11 and 15 years [27]. The prevalence found in our study is higher, which explains the higher gastric cancer incidence found in the North of Portugal [13,28].…”
Section: Discussionmentioning
confidence: 99%
“…In more recent studies, the annual rates were 1.5% in Japan [29], 1.4% in the USA [30], 2.5% in Turkey [31] and 7.0% in Turkish children living in Germany [31,32]. In a study from the South of Portugal, conducted between 2003 and 2006 it was 10.5/100 child-years in the age group 11-15 years [27], though only 52% participated in the follow-up study and from these 60% were lost during the 3-year follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, children living in houses with their own drainage system were more protected from this infection ( p = 0.038; OR = 0.10; 95%CI: 0.02-0.64). Children were also tested for H. pylori infection by antigen stool detection [17], and co-infection was detected in 25 children (p < 0.037; OR = 1.82; 95%CI: 1.05-3.15). A sub-set of children negative for H. pylori infection were monitored every 6 months, during 36 months, in order to evaluate the incidence of H. pylori infection [16].…”
Section: Resultsmentioning
confidence: 99%
“…This study was conducted in the Pediatric clinics at the National Hepatology and Tropical Medicine Research Institute, Abou El-Rish Hospital at Cairo University as well as Benha University Hospital after Institutional Review Board (IRB) approval during the period from July, 2012 to October, 2013. In this cross-sectional study, 80 children was included and presenting with recurrent abdominal pain, which is defined as at least 3 discrete episodes of abdominal pain of sufficient severity to interrupt normal daily activities or performance over H. pylori infection was 31.6% and such rate can increase by age [22] . However, other studies have shown that the prevalence of H. pylori infection in children is independent of age [23,24] .…”
Section: Patientsmentioning
confidence: 99%